Internalisasi Nilai-nilai Akhlak Aktual Melalui Fitrah Based Education (FBD) Bagi Siswa Kelas 1 SDIT Tahfizh Al-Fatih Pekanbaru - Yunita, Yenni; Dian Tri Utami; Kudwatun Nisa; Siti Rofi'atin (Generasi Emas, 2023)
The purpose of this study was to determine the internalization of Actual Moral values ​​through Fitrah Based Education (FBD) for Grade 1 Students of SDIT Tahfizh Al-Fatih Pekanbaru. This research uses a case study method with a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that the education carried out by SDIT Tahfiz Al-Fatih, especially in instilling moral values ​​for students, refers to the concept of FBE (Fitrah Based Education). The fitrahs are 1. Faithfulness, 2. Physical (Physical and healthy) nature, 3. Developmental nature, 4. Learning and Reasoning nature, 5. Sexuality and Love nature, 6. Aesthetic and Language Nature, 7. Talent and nature Leadership, 8. Nature of Individuality and Sociality. Fitrah Based Education (FBE) aims to enable educators and parents to educate their children according to their nature. Included in instilling actual moral values ​​in children starting from grade 1. In addition, PStrengthening the internalization of Actual Moral values ​​applied at SDIT Tahfiz Al-Fatih can also be seen from several school programs, including congregational prayer, the Al-Qur'an program using the ummi method, Tahsin, Muroja'ah, and other extracurricular programs such as pildacil, muhaarah, Art, Fun English and Arabic and so on.